Observe The Response a Finite Element Linear Static Analysis Simulation Was Conducted On The Fire Extinguisher Refill Frame. - Nanda, Rizki Aulia; Karyadi; Mulyadi, Dodi; Suhara, Ade (Universitas Muhammadiyah Sidoarjo, 2025)
The apar refill machine consists of several components so that the frame of the apparatus requires a strength analysis of the frame. The problem that arises to make a portable apparatus is that there are 2 main components that depend and 1 component that does not depend, so the purpose of this study is with the process of finite element linear static analysis, the results of the frame design can show the reactions that arise due to the existing load, whether the frame is safe to use or not. This research method begins with design, material input, mesh input, boundary condition input and force input. The results show that the reactions that occur are the highest stress of 18,882 N, disspacement 2,450E + 00 mm, strain of 8,182E-05 and safety factor 3,6383 + 12. From these results, according to the mechanical properties reference static linear threshold, the value is still safe at the maximum force threshold.